Decreasing incidence of coronary heart disease in extreme obesity (BMI ≥ 40)—A single centre experience. Issue 4 (July 2017) - Barth, Sebastian; Zacher, Michael; Reinecke, Holger; Hautmann, Martina B.; Kerber, Sebastian; Gietzen, Frank; Halbfass, Philipp; Schade, Anja; Deneke, Thomas; Schieffer, Bernhard; Hamm, Karsten
Abstract: Aim: The aim of our comprehensive single centre analysis was to evaluate the incidence of coronary heart disease (CHD) in extremely obese patients. Methods and results: Between 2005 and 2015 we investigated retrospectively 23, 359 patients undergoing cardiac catheterisation in our institution. Patients were divided in six weight classes according to World Health Organization (WHO) criteria [1] (WHO, 2000). Cardiovascular risk factors, comorbidities, CCS stadium [2] (Cox and Naylor, 1992) and NYHA functional class [3] (The Criteria Committee of the New York Heart Association, 1994) were retrieved from electronic patient records. Using multivariable analysis the odds ratio for the target variable CHD with presence of >50% angiographic stenosis was ≥1 with regard to age (OR 1.049, 95% CI 1.045–1.052), male sex (OR 2.507, 95% CI 2.329–2.699), cardiovascular risk factors, atherosclerosis (OR 1.651, 95% CI 1.498–1.820), and presence of angina (OR 4.408, 95% CI 3.892–4.993). NYHA functional class I–IV, absence of angina (OR 0.818, 95% CI 0.729–0.918), and BMI ≥ 40 (OR 0.592, 95% CI 0.494–0.709) resulted in an odds ratio of ≤1. Underweight patients had a higher (5.3%) and overweight (1.2%) and obese patients (class I 0.9% and II 1.1%) a slightly lower all-cause in-hospital mortality compared to extremely obese patients (1.6%). Conclusion: Severely obese patients treated in our hospital surprisingly showed a decreased incidence of CHD (46.1% in normal weight and 38.6% in extremely obese patients) while comorbidities increased CHD as expected. Although CHD burden was lower, obesity and associated comorbidities resulted in higher all-cause—in-hospital mortality.